Detection of full and limited amphidromous migratory dynamics of fish in Caribbean rivers - Frotté, Lou; Ringelstein, Julien; Monti, Dominique; Robert, Marie; Pécheyran, Christophe; Améziane, Nadia; Tabouret, Hélène (Ecology of freshwater fish, 2020)
All native fishes living in the Caribbean island rivers are considered diadromous but few species have been validated as diadromous. In Guadeloupe (Lesser Antilles) as well as in the other tropical islands, the riverine habitats are subject to strong anthropogenic pressure due to resource modifications or dams. The management of fish biodiversity requires knowledge concerning their life history traits and behaviour that are still unknown for most species at a local scale and at the whole distribution area of the species. In a Guadeloupe river, we inferred the migratory patterns of four freshwater fishes common to Caribbean rivers by the analysis of otolith microchemistry. We found two species Eleotris perniger (Eleotridae) and Sicydium plumieri (Gobiidae) to be completely amphidromous with a marine larval phase and a freshwater adult phase. Agonostomus monticola (Mugilidae) was also found to be amphidromous in this system. The fourth species Gobiesox cephalus (Gobiesocidae) showed elemental ratios suggesting an estuarine larval phase and was defined as “limited amphidromous”. The identification of such life history traits, with limited dispersion abilities, argues for specific management measures in tropical island rivers at a basin scale for the conservation of biodiversity.